Periodontal parameters of two types of 3 x 3 orthodontic retainer: a longitudinal study - Larissa A. Ferreira; Diogo M. Sapata; Maria G. A. Provenzano; Roberto M. Hayacibara; Adilson L. Ramos
ABSTRACT Introduction: bonded fixed retainers are often used to stabilize the results obtained with the orthodontic treatment. It is important that they do not prejudice dental health, as they will be used for a long period. Objective: The purpose of the present study was to compare periodontal indexes between two types of bonded fixed retainers, conventional 3 x 3 plain retainer (0.8-mm orthodontic wire, bonded to the canines only) and a manufactured braided retainer (0.2 x 0.7-mm stainless steel wire, bonded to all anterior teeth) after use. Methods: a test group of 15 volunteers (aged from 18 to 25 years) used both the conventional retainer and braided retainer for six months. A randomized longitudinal study design, with a two week washout interval, was applied. The dental plaque index, gingival index and dental calculus index were evaluated. Furthermore, the calculus accumulated along the retainer wire was measured and all patients answered a questionnaire about the use, acceptance and comfort of both types of retainers. Results: the scores for plaque and gingival indexes were higher for the braided retainer (p< 0.05) on the lingual and proximal surfaces. The same occurred with the calculus index on the lingual surfaces (p< 0.05). The calculus index along wire was higher for the braided retainer (p< 0.05). All patients preferred the conventional retainer, and said that it was also more comfortable to use. Conclusion: it was concluded that the conventional retainer showed better periodontal indexes than the braided type.